The Challenge of the Trafficked Girls in the Difficult Process of the Reintegration - Biçoku, Alisa; Denisa Ballhysa (European Journal of Multidisciplinary Studies, 2016)
The reintegration refers to the process of trafficked girls ' involvement in social and economic life. This process, which is important for trafficked women's life remains a long process to achieve. This study focuses on its core trafficked girls who are going through the long high of social reintegration. The aim of this study is to analyze the significance of experiences, emotions, social and economic difficulties that need trafficked girls face during reintegration into society. The specific objective of this study is the importance of the reintegration process and the factors that influence the success of this process in the social life of victims of trafficking. The methodology used in this study is qualitative, as an efficient method that provides a sense of depth to the exploration of subjects, giving us much more detailed and specific information. The tools that have been used are the focus group, organized in collaboration with girls’ victims of trafficking which are secured in the Centre "Vatra".
Keywords: victim of trafficking, reintegration process, assessment.